The Influence of Social Environment and Halal Awareness on Halal Food Purchasing Decisions with Halal Lifestyle as an Intervening Variable: Case Study of Muslim Communities in Toba Regency - Fatmasari, Ellya; Tri Inda Fadhila Rahma; Budi Dharma (Jurnal Manajemen (Edisi Elektronik), 2024)
This study aims to Assess and analyse the influence of social environment and halal awareness on purchasing decisions through halal lifestyle. The object of this research is the Islamic community in Toba Regency. Data collection using area sampling, then questionnaires were distributed to 100 respondents spread across 16 sub-districts in Toba Regency. This research method uses a quantitative approach with associative methods. The data analysis used is statistical analysis in the form of SEM PLS which is tested through outer model analysis and inner model analysis. The results showed that the direct influence of the social environment and halal awareness on purchasing decisions for halal food products had a positive and significant effect. Meanwhile, the indirect effect of the social environment on purchasing decisions for halal food products through a halal lifestyle has a positive and insignificant effect. However, the indirect effect of halal awareness on purchasing decisions through a halal lifestyle has a positive and significant effect. This means that a halal lifestyle cannot intervene in the relationship between the social environment and purchasing decisions, but can intervene in the relationship between halal awareness and purchasing decisions. The implications of this study are the importance of the role of the community in shaping halal consumption behaviour, strengthening education about the concept of halal and the importance of consuming halal products needs to be improved, especially among the younger generation